A 12‐Year‐Old Child With a Sunken Sternum and Progressive Muscle Weakness: A Case Report - Siman Chen; Chenghao Chen; Qi Zeng (Clinical Case Reports, 2026)
ABSTRACT A 12‐year‐old girl with facioscapulohumeral muscular dystrophy and severe pectus excavatum presented with progressive dyspnea and restrictive ventilatory impairment. She underwent successful Nuss repair with uneventful recovery. At 6‐month follow‐up, chest contour and pulmonary function improved, suggesting that surgical correction is feasible and beneficial in FSHD when mechanical restriction predominates.